Ceramic filter membrane and preparation method thereof

By using phase separation technology in the ceramic filter membrane to form step-shaped holes, the problem of difficulty in taking into account both the flux and strength of the ceramic filter membrane is solved, and a high-throughput and high-strength ceramic filter membrane is achieved, extending the service life and improving reliability.

CN119565400APending Publication Date: 2025-03-07LANDSON MEMBRANE TECH NANJING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411810293.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

While increasing the flux, existing ceramic filter membranes are difficult to maintain high strength, resulting in insufficient service life and reliability.

Method used

By using phase separation technology, the incomplete reaction of poor solvents with the phase separation agent is controlled to form step-shaped pores, which not only ensures the flux of the filter membrane but also increases its strength.

Benefits of technology

It realizes that while ensuring flux, the ceramic filter membrane significantly improves its strength, extends its service life, and improves reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565400A_ABST
    Figure CN119565400A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a ceramic filter membrane, which comprises the following steps: uniformly mixing a binder, a dispersant, a lubricant, a phase separation agent and deionized water to obtain a mixed solution, pouring the mixed solution and ceramic powder into a ball milling tank, carrying out ball milling and mixing for a period of time, adding a defoaming agent, and continuing ball milling to obtain a ceramic filter membrane; carrying out ice-bath vacuum stirring and defoaming on the ball-milled slurry to obtain a membrane preparation solution; carrying out tape casting on the obtained film preparation liquid on the surface of a ceramic matrix to prepare a cast film layer; immersing the ceramic matrix with the cast film layer in a poor solvent, taking out the ceramic matrix, and drying the ceramic matrix at room temperature to obtain a filter layer; wherein the poor solvent is ensured to be incompletely reacted with the phase separating agent in the cast film layer; and calcining the dried ceramic matrix to obtain the required ceramic filter membrane. According to the method, the poor solvent and the phase separating agent are controlled to react incompletely to form the stepped pore channels, so that the strength of the filtering membrane is improved while the flux of the filtering membrane is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic filter membranes, and in particular to a ceramic filter membrane and a preparation method thereof. Background Art

[0002] Ceramic membrane is a new type of membrane separation technology, generally composed of a porous ceramic matrix and a transition layer and filter layer loaded on the matrix. Its operating principle is to achieve separation and purification of substances based on the pressure difference on both sides of the membrane. Ceramic membrane has the advantages of long service life and less burden of cleaning and maintenance. Its operation basically does not require heat energy and chemical reactions. It is a filtration technology that can operate under normal temperature physical conditions. Therefore, ceramic membrane can be widely used in the production of food, medicine, health care and other fields, and can also provide environmental protection treatment technology for some industrial wastewater.

[0003] Ceramic membranes are generally composed of a support layer, a transition layer, and a membrane layer (filter layer). Therefore, they need to be sintered three times during preparation, and the sintering cost accounts for up to 60%, which leads to excessively high preparation costs. In terms of performance, the filtration layer of the ceramic membrane determines the filtration accuracy of the ceramic membrane. For ceramic filter layers with excellent performance, not only the cost issue should be considered, but also the permeability and selectivity of the filter layer. The selectivity of the filter layer determines the separation accuracy of the ceramic membrane, which is mainly related to the pore size and distribution of the filter layer. The conventional method of preparing the ceramic filter layer adopts the particle stacking method, which has poor pore continuity. In order to obtain high flux, the porosity is usually high, and it is easy to form a macroporous structure, and the strength of the ceramic membrane is low.

[0004] Phase separation technology utilizes the difference in solubility of polymers under different conditions, and separates the polymers from the homogeneous solution by changing factors such as temperature and solvent composition, forming a membrane with a certain pore structure. The membrane layer prepared by this method has good pore continuity, uniform pore size distribution, and high porosity, but the high porosity sacrifices the strength of the membrane, affecting the reliability and service life of the ceramic membrane. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a ceramic filter membrane in order to address the problem in the prior art that the filter membrane has high flux but cannot have high strength at the same time. The method adopts phase separation technology and controls the incomplete reaction of a poor solvent and a phase separation agent to form a stepped pore channel, thereby improving the strength of the filter membrane while ensuring the flux of the filter membrane.

[0006] According to a first aspect of the present invention, there is provided a method for preparing a ceramic filter membrane, comprising the following steps:

[0007] S1. Mix a binder, a dispersant, a lubricant, a phase separation agent and deionized water to obtain a mixed solution, pour the mixed solution and ceramic powder into a ball mill, add a defoamer and continue ball milling after mixing for a period of time, and perform vacuum stirring in an ice bath to remove bubbles in the ball-milled slurry to obtain a film-making solution;

[0008] S2, applying the film-making liquid obtained in step S1 to the surface of the ceramic substrate by tape casting to prepare a cast film layer;

[0009] S3, immersing the ceramic substrate with the cast film layer obtained in step S2 in a poor solvent, and then taking it out and drying it at room temperature to obtain a filter layer; wherein, it is ensured that the poor solvent does not react completely with the phase separation agent in the cast film layer, and the precipitated phase formed becomes less and less as the reaction proceeds, thereby forming a stepped channel in the cast film, and the pore size of the stepped channel tends to gradually decrease from one end close to the ceramic substrate to the outside;

[0010] S4, calcining the ceramic substrate dried in step S3 to obtain the desired ceramic filter membrane.

[0011] As an optional embodiment, the components in the membrane-making solution, calculated in percentage by mass, include: 40% to 65% ceramic powder, 1% to 5% binder, 0.5% to 2% dispersant, 0.5% to 3% lubricant, 0.1% to 3% phase separator, 0.2% to 0.8% defoamer, and 19.7% to 57.3% deionized water; the defoamer accounts for 0.2% to 0.8% of the total mass of the mixed solution and ceramic powder.

[0012] As an optional embodiment, the ceramic powder is one or more of aluminum oxide, silicon carbide, zirconium oxide, silicon oxide and titanium oxide.

[0013] As an optional embodiment, the median particle size D50 of the ceramic powder is 0.3-30 μm.

[0014] As an optional embodiment, the phase separation agent is PEO, and the molecular weight is 100,000 to 1,000,000.

[0015] As an optional embodiment, the binder is one or more of PVA, HPMC, CMC and polyacrylic acid, the dispersant is PVP and / or sodium polyacrylate, and the lubricant is polyethylene glycol.

[0016] As an optional implementation, the specific process of step S2 is as follows: pour the film-making liquid onto the ceramic substrate and use a scraper to scrape it, wherein the height of the scraper from the ceramic substrate is 0.1 to 1 mm, the scraper speed is 1-20 mm / s, the ambient temperature is controlled at 22±2°C, and the ambient humidity is controlled at 60±5RH.

[0017] As an optional implementation, the poor solvent is ethanol, and the mass ratio of the poor solvent to the ceramic matrix is ​​(0.1-0.2):1.

[0018] As an optional embodiment, the ceramic substrate with the cast film layer is immersed in a poor solvent under the following conditions: standing at a temperature of 20 to 25° C. for 4 to 24 hours.

[0019] As an optional embodiment, in step S4, the calcination conditions are: heating to 200°C at a rate of 0.5°C / min and keeping warm for 1 hour; then heating to 500°C at a rate of 2°C / min and keeping warm for 1 hour; finally heating to 1300°C at a rate of 5°C / min and keeping warm for 3 to 4 hours.

[0020] As an optional embodiment, the material of the ceramic matrix is ​​one or more of aluminum oxide, silicon carbide, zirconium oxide, silicon oxide and titanium oxide, with a porosity of 30% to 45% and a pore size of 2 to 50 μm.

[0021] According to a second aspect of the present invention, there is provided a ceramic filtration membrane prepared by the aforementioned method.

[0022] As an optional embodiment, the ceramic filter membrane is composed of a ceramic substrate with micropores and a filter layer with micropores; wherein the pore size of the micropores in the filter layer gradually decreases from one end close to the ceramic substrate to the outside, forming a stepped channel.

[0023] As an optional embodiment, the average pore size of the micropores in the filter layer is 1.5 to 2 μm.

[0024] It can be seen from the above technical scheme of the present invention that in the preparation method of the ceramic filter membrane proposed by the present invention, the poor solvent gradually penetrates upward in the matrix to separate the phase separation agent from the message membrane layer, and by controlling the amount of the poor solvent, it is ensured that the poor solvent will not completely react with the phase separation agent in the membrane layer. The poor solvent and the solvent replacement will continue to be consumed over time, the proportion of the poor solvent will become lower and lower, the reaction rate will gradually decrease, the formed precipitated phase will gradually decrease, and the formed pores will become smaller and smaller, thereby obtaining a stepped pore structure with a pore size that gradually decreases from one end close to the ceramic matrix to the outside.

[0025] The ceramic filter membrane prepared by the method of the present invention has a gradually smaller stepped pore structure with reduced porosity, thereby improving the strength of the ceramic filter membrane. However, when filtering, after the filtered liquid passes through the small holes at the upper end, the resistance of the pipeline is reduced and the flux becomes larger, thereby ensuring the high flux of the ceramic filter membrane. In this way, the ceramic filter membrane improves the strength of the filter membrane while ensuring the flux of the filter membrane, thereby improving the reliability and service life of the ceramic filter membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of the ceramic filter membrane prepared by the method of the present invention.

[0027] Figure 2 is a SEM image of the sample of Example 1 of the present invention.

[0028] Figure 3 This is a pore size distribution diagram of the sample of Invention Example 1. DETAILED DESCRIPTION

[0029] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.

[0030] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.

[0031] In an exemplary embodiment of the present invention, a method for preparing a ceramic filter membrane is provided, comprising the following steps:

[0032] S1. Mix the binder, dispersant, lubricant, phase separation agent and deionized water evenly to obtain a mixed solution, pour the mixed solution and ceramic powder into a ball mill, mix them for a period of time, add a defoamer and continue to ball mill, and stir the milled slurry in an ice bath vacuum to remove bubbles to obtain a film-making solution.

[0033] S2, preparing a cast film layer by casting the film-making liquid obtained in step S1 on the surface of a ceramic substrate.

[0034] S3. Immersing the ceramic substrate with the cast membrane layer obtained in step S2 in a poor solvent, then taking it out and drying it at room temperature to obtain a filter layer; wherein, it is ensured that the poor solvent does not react completely with the phase separation agent in the cast membrane layer, and the precipitated phase formed becomes less and less as the reaction proceeds, thereby forming a stepped channel in the cast membrane, and the pore size of the stepped channel tends to gradually decrease from one end close to the ceramic substrate to the outside.

[0035] S4, calcining the ceramic substrate dried in step S3 to obtain the desired ceramic filter membrane.

[0036] As an optional example, the viscosity requirement of the film-making solution is: at 22° C., the viscosity at 100 rpm is 300 to 3200 cps.

[0037] As an optional example, the components in the film-making solution, calculated in percentage by mass, include: 40% to 65% ceramic powder, 1% to 5% binder, 0.5% to 2% dispersant, 0.5% to 3% lubricant, 0.1% to 3% phase separator, and 19.7% to 57.3% deionized water; the defoaming agent accounts for 0.2% to 0.8% of the total mass of the mixed solution and ceramic powder.

[0038] By controlling the viscosity of the film-making liquid through component selection, the film-making liquid can penetrate into the ceramic matrix to a certain depth to provide adhesion, but will not penetrate too deeply to block the pores, thereby achieving the purpose of omitting the transition layer, performing two-step molding and sintering, and reducing production costs.

[0039] As an optional example, the ceramic powder is one or more of aluminum oxide, silicon carbide, zirconium oxide, silicon oxide and titanium oxide.

[0040] As an optional example, the median particle size D50 of the ceramic powder is 0.3 to 30 μm, and particularly preferably 0.3 to 0.4 μm.

[0041] As an optional example, the phase separation agent is PEO, and the molecular weight is 100,000 to 1,000,000.

[0042] As an optional example, the binder is one or more of PVA, HPMC, CMC and polyacrylic acid.

[0043] As an optional example, the dispersant is PVP and / or sodium polyacrylate, and the lubricant is polyethylene glycol.

[0044] It can be understood that the defoaming agent can be selected from any common defoaming agent in the art and is not further limited herein.

[0045] As an optional example, the specific process of step S2 is as follows: pour the film-making liquid onto the ceramic substrate and use a scraper to scrape it, wherein the height of the scraper from the ceramic substrate is 0.1 to 1 mm, the scraper speed is 1-20 mm / s, the ambient temperature is controlled at 22±2°C, and the ambient humidity is controlled at 60±5RH.

[0046] As an optional example, the poor solvent is ethanol, and the mass ratio of the poor solvent to the ceramic matrix is ​​(0.1-0.2):1.

[0047] As an optional example, the ceramic substrate with the cast film layer is immersed in a poor solvent under the following conditions: standing at a temperature of 20 to 25° C. for 4 to 24 hours.

[0048] As an optional example, in step S4, the calcination conditions are: heating to 200°C at a rate of 0.5°C / min and keeping warm for 1 hour; then heating to 500°C at a rate of 2°C / min and keeping warm for 1 hour; finally heating to 1300°C at a rate of 5°C / min and keeping warm for 3 to 4 hours.

[0049] As an optional example, the material of the ceramic matrix is ​​one or more of aluminum oxide, silicon carbide, zirconium oxide, silicon oxide and titanium oxide, with a porosity of 30% to 45% and a pore size of 2 to 50 μm.

[0050] It can be understood that the ceramic matrix can be selected according to actual needs.

[0051] In another exemplary embodiment of the present invention, a ceramic filtration membrane prepared by the aforementioned method is also provided.

[0052] like Figure 1 As shown, as an optional example, the ceramic filter membrane is composed of a ceramic substrate 1 with micropores and a filter layer 2 with micropores; wherein the pore size of the micropores in the filter layer gradually decreases from one end close to the ceramic substrate to the outside, forming a stepped pore example, and the average pore size of the micropores in the filter layer is 1.5 to 2 μm.

[0053] For better understanding, the present invention is further described below in conjunction with several specific examples, but the preparation process is not limited thereto, and the content of the present invention is not limited thereto.

[0054] Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.

[0055] In the following examples and comparative examples, the ceramic substrate used is alumina with a porosity of 40%, a pore size of 15 μm, and a surface roughness of less than 5 μm.

[0056] The ceramic powder is alumina powder, D10: 5 μm, D50: 8 μm, D90: 14 μm.

[0057] The adhesive is PVA217 Japanese Kuraray.

[0058] The dispersant is Zhongjing Oil D305.

[0059] The phase separation agent is PEO with a molecular weight of 1 million.

[0060] The defoaming agent is D485.

[0061] The samples of the following examples and comparative examples were prepared as follows:

[0062] Ball milling: Add adhesive, dispersant, lubricant, phase separation agent, and solvent (deionized water) into a container, stir and disperse at a speed of 300 rpm for 1.5 hours to obtain solution A; pour the ceramic powder and solution A into a ball mill and ball mill for 8 hours; add a defoaming agent 10 minutes before discharging, the proportion of which is 0.4% of the slurry mass, and after discharging, stir and remove bubbles in an ice bath under vacuum for 0.5 hours.

[0063] Casting: The ceramic substrate is placed at the bottom, the scraper is 0.8 mm high from the ceramic substrate, the scraper speed is 10 mm / s, and the ambient temperature and humidity are controlled at 22±2℃, 60±5RH.

[0064] Phase separation: The ceramic membrane substrate with the cast layer was immersed in a flat-bottomed container filled with a poor solvent (ethanol), left to stand at 25°C for 10 hours, and then taken out and dried at room temperature for 3 days.

[0065] Degreasing and sintering: Place the dried ceramic membrane in a muffle furnace, heat it to 200°C at a rate of 0.5°C / min, and keep it warm for 1 hour; heat it to 500°C at a rate of 2°C / min, and keep it warm for 1 hour; heat it to 1300°C at a rate of 5°C / min, and keep it warm for 3 hours.

[0066] The contents of each component in Examples 1-9 and Comparative Examples 1-2 are shown in Table 1

[0067] Table 1

[0068]

[0069] Note: The test conditions for slurry viscosity are: 22°C, 100rpm.

[0070] SEM Testing

[0071] The sample of Example 1 was subjected to SEM test, and the results were as follows: Figure 2 shown.

[0072] As can be seen from the figure, the sample pores of the present invention have good connectivity, high flux, and the particles are fully and smoothly connected, thus ensuring the strength of the filter membrane.

[0073] Aperture test

[0074] The sample of Example 1 was tested for the pore size of the filter layer, and the results were as follows: Figure 3 shown.

[0075] As can be seen from the figure, the pore size in the filter membrane is between 1.5-2μm, with good concentration and no large pores, thus ensuring the high filtration efficiency of the ceramic filter membrane, and pollutants will not leak through due to large pores, and the filtration accuracy is high.

[0076] Performance Testing

[0077] The samples obtained in Examples 1-9 and Comparative Examples 1-2 were tested for flux and strength, and the results are shown in Table 2.

[0078] Table 2

[0079] <![CDATA[Flux (L / (kpa*cm 2 *min))]]> Strength (100 grid test) Example 1 2.58 90 Example 2 1.86 91 Example 3 3.21 87 Example 4 4.15 62 Example 5 4.55 52 Example 6 4.36 59 Example 7 1.14 96 Example 8 1.27 93 Example 9 0.95 97 Comparative Example 1 3.76 28 Comparative Example 2 0.81 98

[0080] It can be seen from Table 2 that the ceramic filter membrane prepared by the method of the present invention improves the strength of the filter membrane while ensuring the filter membrane flux, and improves the reliability and service life of the ceramic filter membrane.

[0081] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A method for preparing a ceramic filter membrane, characterized in that: The following steps are involved: S1. Mix a binder, a dispersant, a lubricant, a phase separation agent and deionized water to obtain a mixed solution, pour the mixed solution and ceramic powder into a ball mill, add a defoamer and continue ball milling after mixing for a period of time, and perform vacuum stirring in an ice bath to remove bubbles in the ball-milled slurry to obtain a film-making solution; S2, applying the film-making liquid obtained in step S1 to the surface of the ceramic substrate by tape casting to prepare a cast film layer; S3, immersing the ceramic substrate with the cast film layer obtained in step S2 in a poor solvent, and then taking it out and drying it at room temperature to obtain a filter layer; wherein, it is ensured that the poor solvent does not react completely with the phase separation agent in the cast film layer, and the precipitated phase formed becomes less and less as the reaction proceeds, thereby forming a stepped channel in the cast film, and the pore size of the stepped channel tends to gradually decrease from one end close to the ceramic substrate to the outside; S4, calcining the ceramic substrate dried in step S3 to obtain the desired ceramic filter membrane.

2. The preparation method according to claim 1, characterized in that: The components in the film-making solution, calculated by mass percentage, include: 40% to 65% ceramic powder, 1% to 5% binder, 0.5% to 2% dispersant, 0.5% to 3% lubricant, 0.1% to 3% phase separator, and 19.7% to 57.3% deionized water; the defoaming agent accounts for 0.2% to 0.8% of the total mass of the mixed solution and the ceramic powder.

3. The preparation method according to claim 1, characterized in that: The ceramic powder is one or more of aluminum oxide, silicon carbide, zirconium oxide, silicon oxide and titanium oxide.

4. The preparation method according to claim 1, characterized in that: The median particle size D50 of the ceramic powder is 0.3 to 30 μm.

5. The preparation method according to claim 1, characterized in that: The phase separation agent is PEO, and the molecular weight is 100,000 to 1,000,000.

6. The preparation method according to claim 1, characterized in that: The binder is one or more of PVA, HPMC, CMC and polyacrylic acid, the dispersant is PVP and / or sodium polyacrylate, and the lubricant is polyethylene glycol.

7. The preparation method according to claim 1, characterized in that: The specific process of step S2 is as follows: pour the film-making liquid on the ceramic substrate and use a scraper to scrape it, wherein the height of the scraper from the ceramic substrate is 0.1-1mm, the scraper speed is 1-20mm / s, the ambient temperature is controlled at 22±2℃, and the ambient humidity is controlled at 60±5RH.

8. The preparation method according to claim 1, characterized in that: The poor solvent is ethanol, and the mass ratio of the poor solvent to the ceramic matrix is ​​(0.1-0.2):

1.

9. The preparation method according to claim 1, characterized in that: The conditions for immersing the ceramic substrate with the cast film layer in the poor solvent are: standing at a temperature of 20 to 25° C. for 4 to 24 hours.

10. The preparation method according to claim 1, characterized in that: In step S4, the calcination conditions are: heating to 200°C at a rate of 0.5°C / min and keeping warm for 1 hour; then heating to 500°C at a rate of 2°C / min and keeping warm for 1 hour; finally heating to 1300°C at a rate of 5°C / min and keeping warm for 3 to 4 hours.

11. The preparation method according to any one of claims 1 to 10, characterized in that: The material of the ceramic matrix is ​​one or more of aluminum oxide, silicon carbide, zirconium oxide, silicon oxide and titanium oxide, with a porosity of 30% to 45% and a pore size of 2 to 50 μm.

12. A ceramic filtration membrane prepared by the method according to any one of claims 1 to 11.

13. The ceramic filtration membrane according to claim 12, characterized in that: The ceramic filter membrane is composed of a ceramic substrate with micropores and a filter layer with micropores; wherein the pore size of the micropores in the filter layer gradually decreases from one end close to the ceramic substrate outwards to form a stepped channel.

14. The ceramic filtration membrane according to claim 13, characterized in that The average pore size of the micropores in the filter layer is 1.5 to 2 μm.